Performance Analysis of Modified SVPWM Strategies for Three Phase Cascaded Multi-level Inverter fed Induction Motor Drive - Ravikumar Bhukya; P. Satish Kumar (Institute of Advanced Engineering and Science, 2017)
This paper presents new modified space vector pulse width modulation techniques (Phase disposition-Space vector pulse width modulation, Alternative Phase Opposition disposition- Space vector pulse width modulation and Phase Opposition disposition-Space vector pulse width modulation) are analyzed for three-phase cascaded multi-level inverter fed induction motor from the point of view of the Phase voltages, line voltage, stator current,speed,torque and Total harmonic distortion.in the proposed modified technique the reference signals are generated by adding offset voltage to the reference phase voltages.This modified SVPWM technique does not involve region indentification,sector identification for switching vector determination as are required in the conventional multi level SVPWM technique,it is also reduces the computation time compared to the conventional space vector PWM technique.The necessary calculations for generation of new modified SVPWM for the modulation strategies have presented in detail. It is observed that the modified SVPWM modulation ensures excellent, close to optimized pulse distribution results and THD is compared to for five-level, seven-level, nine-level and eleven-level Cascaded H-Bride Multi-level Inverter fed to Induction motor. Theoretical investigations were confirmed by the digital simulations using MATLAB/SIMULINK software.